2022
DOI: 10.3390/bioengineering9110717
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell- and Cell-Based Therapies for Ischemic Stroke

Abstract: Stroke is the second cause of disability worldwide as it is expected to increase its incidence and prevalence. Despite efforts to increase the number of patients eligible for recanalization therapies, a significant proportion of stroke survivors remain permanently disabled. This outcome boosted the search for efficient neurorestorative methods. Stem cells act through multiple pathways: cell replacement, the secretion of growth factors, promoting endogenous reparative pathways, angiogenesis, and the modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…Cell therapy, which involves the use of primary cells, cell lines and various stem cells, has been a promising method for the treatment of difficult diseases in recent years 34 . Through transplantation and local infusion of autologous or allogeneic cells, cells and/or biologically active molecules are used to repair or enhance the biological function of damaged tissues 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapy, which involves the use of primary cells, cell lines and various stem cells, has been a promising method for the treatment of difficult diseases in recent years 34 . Through transplantation and local infusion of autologous or allogeneic cells, cells and/or biologically active molecules are used to repair or enhance the biological function of damaged tissues 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell transplantation is a research hotspot in the field of ischemic stroke treatment. Stem cells have the advantage of low immunogenicity, can differentiate into many types of cells as needed, and can replace damaged brain cells, thus making them the first choice for cell transplantation [ 126 ]. There are various types of stem cells used in stroke research, such as neural stem cells and mesenchymal stem cells (MSCs).…”
Section: Applications Of Plga-based Nanostructures In Cell Transplant...mentioning
confidence: 99%
“…Honmou et al reported that there were no major side events after the intravenous infusion of autologous BMSCs expanded in human serum into 12 participants 36-133 days post-stroke (Honmou et al, 2011). Overwhelming evidence supports the safety of the approach, although data on its efficacy are scarce or indicate only a transient improvement (Nistor-Cseppentö et al, 2022). Majority of the adverse events in these clinical trials were minor (Kvistad et al, 2022).…”
Section: Clinical Application Prospect Of Stem Cells In Strokementioning
confidence: 99%